2019
DOI: 10.3390/w11051042
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires in Grasslands and Shrublands: A Review of Impacts on Vegetation, Soil, Hydrology, and Geomorphology

Abstract: Wildfires are prevalent in grasslands and shrublands. The objective of this study is to provide land managers with a general overview, by assessing the main impacts of wildfire, including those on plant communities (e.g., secondary succession and species invasion), soil characteristics (e.g., water repellency (hydrophobicity), aggregation and structure stability, and contents of organic carbon and nutrients), and surface processes (e.g., ash deposition, ground surface clogging, water runoff, soil erosion, hill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 83 publications
3
55
0
Order By: Relevance
“…As numerous studies have shown, the impact of wildfires on vegetation depends on many factors such as the seasonality of burning (Wright, 1974), the presence of different phenological stages at the burn time (Ruckman et al, 2012) and of the dominant type of vegetation. The shrubland vegetation, which dominates the surroundings of Lakes Skadar/Shkodra and Šas that were exposed to fires, is generally characterized by low-to-moderate fuel loads resulting in a relatively lower fire intensity, and consequently a relatively moderate impact on the soil (Stavi, 2019). For example, Malkinson & Wittenberg (2015) reported neutral to a positive effect of wildfires on vegetation in the dry, sub-humid north of Israel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As numerous studies have shown, the impact of wildfires on vegetation depends on many factors such as the seasonality of burning (Wright, 1974), the presence of different phenological stages at the burn time (Ruckman et al, 2012) and of the dominant type of vegetation. The shrubland vegetation, which dominates the surroundings of Lakes Skadar/Shkodra and Šas that were exposed to fires, is generally characterized by low-to-moderate fuel loads resulting in a relatively lower fire intensity, and consequently a relatively moderate impact on the soil (Stavi, 2019). For example, Malkinson & Wittenberg (2015) reported neutral to a positive effect of wildfires on vegetation in the dry, sub-humid north of Israel.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Malkinson & Wittenberg (2015) reported neutral to a positive effect of wildfires on vegetation in the dry, sub-humid north of Israel. Most studies that have addressed the impact of fire on vegetation have shown that this impact is highly site-specific and can be either negative or positive (Deák et al, 2014;Stavi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, afforestation and reforestation projects are more successful when comprised of mixed tree species, which are less susceptible to infestation by pests and diseases than single-species plantations [25]. Regardless, the increase in frequency and intensity of droughts around the world, driven by climate change, lead to mass drying and mortality of trees, resulting in increased incidence and aggravated intensity of wildfires [26,27]. Therefore, preference should be given for the selection of drought-tolerant, fire-resistant, and less flammable tree species [28].…”
Section: Low-impact Forestrymentioning
confidence: 99%
“…Studies in forest ecosystems have shown that total land area burned and area burned at high severity increased in general (Dillon et al., 2011; Rollins, 2009; Singleton et al., 2019), while trends in the proportion of areas burned at high severity varied among regions in western United States (Miller et al., 2012; Nigro & Molinari, 2019). Although wildfires are common and extensive in many rangelands which are fire‐dependent ecosystems (Fuhlendorf et al., 2011), rangelands have low to moderate fuel loads compared to forests and tend to have fires with low and moderate burn severity (Stavi, 2019).…”
Section: Introductionmentioning
confidence: 99%